2009
DOI: 10.1002/cncr.24445
|View full text |Cite
|
Sign up to set email alerts
|

MEKK3 expression correlates with nuclear factor κ B activity and with expression of antiapoptotic genes in serous ovarian carcinoma

Abstract: Coffee, tea and maté may cause esophageal cancer (EC) by causing thermal injury to the esophageal mucosa. If so, the risk of EC attributable to thermal injury could be large in populations in which these beverages are commonly consumed. In addition, these drinks may cause or prevent EC via their chemical constituents. Therefore, a large number of epidemiologic studies have investigated the association of an indicator of amount or temperature of use of these drinks or other hot foods and beverages with risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 117 publications
3
23
1
Order By: Relevance
“…Breast tumors that express high levels of MEKK3 have correspondingly high NF-κB binding activities, whereas tumors with low MEKK3 levels have low constitutive NF-κB binding activities, comparable with those of normal control breast tissues. This was consistent with reports by Samanta et al (21,22). Many types of cancer that have constitutively elevated NF-κB binding activity are resistant to apoptosis by conventional chemotherapies (25,26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Breast tumors that express high levels of MEKK3 have correspondingly high NF-κB binding activities, whereas tumors with low MEKK3 levels have low constitutive NF-κB binding activities, comparable with those of normal control breast tissues. This was consistent with reports by Samanta et al (21,22). Many types of cancer that have constitutively elevated NF-κB binding activity are resistant to apoptosis by conventional chemotherapies (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…However, except for MEKK3, genetic studies have raised uncertainties regarding their involvement in the activation of NF-κB (20,21). Furthermore, studies have shown that overexpression of MEKK3 activates the NF-κB pathways (21,22). Recent studies showed that dysregulation of MEKK3 can affect NF-κB activation (23).…”
Section: Rnai Silencing Of the Mekk3 Gene Promotes Trailinduced Apoptmentioning
confidence: 99%
“…In neoplasms, NF-κB has received specific attention for its role in oncogenesis (1)(2)(3)(4)(5). In addition, inducible chemoresistance is attributed to the activation of NF-κB, which in turn stimulates the transcription of anti-apoptotic genes enabling cells to overcome chemotherapy-induced apoptosis (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…One of the causes of chemoresistance is known to be upregulation of anti-apoptotic markers such as Bcl-2 and Bcl-xL, and this effect requires signaling through NF-κB (16,17). To determine whether the sensitization of SGC-7901 to chemotherapeutic agents was due to the downregulation of NF-κB and therefore, of Bcl-2 and Bcl-xL, we examined the levels of Bcl-2 and Bcl-xL.…”
Section: Chemotherapeutics Induce Apoptosis Jointly Using Curcumin Imentioning
confidence: 99%
“…AKT pathway activation induced by MAP17 expression may explain some of the properties described here. Under certain conditions, an increase in AKT activity may lead to a decrease in p38 phosphorylation; a decrease in AKT may lead to an increase in p38a phosphorylation, possibly through the release of the activity of p38 upstream kinases (most likely ASK1 and MEKK3) (Samanta et al, 2009). This relationship is further supported by the strong direct correlation between MAP17 levels and AKT phosphorylation and by the p38a dephosphorylation in breast tumors found in this work ( Figure 6) and by others (Huang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%